Apoptosis contributes to protect germ cells from the oogenic germline starvation response but is not essential for the gonad shrinking or recovery observed during adult reproductive diapause in C. elegans - Carranza-García, E. (PLoS One, 2019)
When C. elegans hermaphrodites are deprived of food during the mid-L4 larval stage and throughout adulthood, they enter an alternative stage termed “adult reproductive diapause (ARD)” in which they halt reproduction and extend their lifespan. During ARD, germ cell proliferation stops; oogenesis is slowed; and the gonad shrinks progressively, which has been described as the “oogenic germline starvation response”. Upon refeeding, the shrunken gonad is regenerated, and animals recover fertility and live out their remaining lifespan. Little is known about the effects of ARD on oocyte quality after ARD. Thus, the aim of this study was to determine how oocyte quality is affected after ARD by measuring brood size and embryonic lethality as a reflection of defective oocyte production. We found that ARD affects reproductive capacity. The oogenic germline starvation response protects oogenic germ cells by slowing oogenesis to prevent prolonged arrest in diakinesis. In contrast to a previous report, we found that germ cell apoptosis is not the cause of gonad shrinkage; instead, we propose that ovulation contributes to gonad shrinkage during the oogenic germline starvation response. We show that germ cell apoptosis increases and continues during ARD via lin-35/Rb and an unknown mechanism. Although apoptosis contributes to maintain germ cell quality during ARD, we demonstrated that apoptosis is not essential to preserve animal fertility. Finally, we show that IIS signaling inactivation partially participates in the oogenic germline starvation response.